MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP PECAHAN SISWA KELAS IV SD MELALUI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) - Sintia Yesepa; Bahri, Samsul; Nurlaili, Nurlaili; Hafiz, Tanzil (Universitas Negeri Medan, 2024)
This study aims to enhance the conceptual understanding of fractions among fourth-grade students at SD Negeri 060910 Medan Denai through the implementation of the Culturally Responsive Teaching (CRT) approach. This approach emphasizes the importance of incorporating local culture into the learning process to create more meaningful connections for students. The method used in this research is Classroom Action Research (CAR), conducted in two cycles. Data were collected through observations, interviews, and conceptual understanding tests. The findings indicate a significant improvement in students’ comprehension of fractions following the application of CRT, both in terms of cognitive achievement and active participation in learning activities.